Performance of polyvinyl ether based nanolubricants in residential air conditioning - Mohd Farid, Ismail (2022)
Residential air conditioning (RAC) is a home appliance that contributes to high energy consumption. The endeavour toward efficient RAC is vital in fulfilling the purpose of utilising the energy effectively. One unique technique to encounter this challenge is by dispersing nanoparticles in the RAC lubricant, namely nanolubricant. Nanolubricant application in the RAC system can improve the properties of pure lubricants and enhance the performance of RAC systems. The present study aims to examine the thermo-physical and tribological properties of Polyvinyl ether (PVE) based nanolubricants dispersed with SiO2 and TiO2 nanoparticles, evaluate the performance of RAC operated with mono and hybrid nanolubricants, and investigate the optimum condition of RAC system performance using nanolubricant. The nanoparticles were dispersed in the PVE lubricant with up to 0.1% concentrations using the two-step method preparation. The stability of nanolubricants was evaluated by qualitative and quantitative methods. The rheological property of nanolubricants was measured at temperatures of 30 to 100 °C, while the thermal conductivity property was investigated up to 80 °C. The tribological property of nanolubricants was tested using the four-ball method that conforms to the ASTM D4172 standards. The experimental investigation for the RAC performance was conducted in a customised RAC test rig together with a thermal control room. The optimization was carried out using response surface methodology while regression models for the operating parameters were formulated. The RAC system input parameters were optimised for the outdoor temperature and concentration range of 31 to 39 °C and 0 to 0.007%, respectively. Stability evaluation showed that all nanolubricants have excellent stability attributes with limited sedimentation observed within 30 days. The ultraviolet-visible spectroscopy results revealed that the TiO2/PVE nanolubricants showed the best stability results with 95% concentration ratio up to 30 days. The zeta potential values for all types of nanolubricants were more than 60 mV. Dynamic viscosity and thermal conductivity of the mono and hybrid nanolubricants increased with volume concentration but decreased with temperature. The maximum viscosity was increased by 2% for all nanolubricants at all temperatures. An exciting finding happened at 30 °C, where the viscosity of nanolubricants was decreased compared to pure PVE. A maximum 2.7% thermal conductivity increment was found at 0.01% concentration of TiO2/PVE nanolubricant. Promising tribological results were obtained from nanolubricants with the concentration of 0.005% and 0.015% for SiO2/PVE and TiO2/PVE, respectively, with the coefficient of friction reduction up to 15%. Performance improvements were found for almost all tested samples when nanolubricants were applied in the RAC system. Nanolubricants have contributed to compressor work reduction, cooling capacity enhancement, and power consumption reduction of the RAC system. The maximum coefficient of performance and energy efficiency ratio enhancement were achieved at 39.25% and 52.74%, respectively, for SiO2-TiO2/PVE nanolubricant at 0.005% concentration. The optimization results for the SiO2-TiO2/PVE nanolubricants yield optimum compressor work, cooling capacity and power consumption of 29.322 kJ/kg, 4.564 kW and 0.774 kW, respectively, at the highest desirability of 0.913. The optimisation exercise found 0.043% was the optimum concentration for SiO2-TiO2/PVE nanolubricants. In conclusion, nanolubricants enhanced the properties of PVE lubricant and improved the performance of the RAC system operating with R32 refrigerant. The SiO2-TiO2/PVE nanolubricant with a concentration of 0.043% is recommended for the optimum performance of the RAC system.